Role of radiotherapy in the treatment of primary mediastinal large B-cell lymphoma - WANG, JINGJING (Oncol Lett, 2015)
The role of radiotherapy (RT) in the treatment of primary mediastinal large B-cell lymphoma (PMLBCL) is unclear. In the present study, a retrospective analysis of 63 patients with PMLBCL treated with or without RT was performed to evaluate the role of RT. Clinical outcomes were calculated using the Kaplan-Meier method and were compared between patients who did and did not receive RT, using the log-rank test. A multivariate analysis was performed using Cox proportional hazards model. After chemotherapy, 35 patients received RT, and RT was found to be associated with significantly improved 5-year overall survival (OS) (87 vs. 58%; P=0.001) and 5-year progression-free survival (PFS) (75 vs. 39%; P=0.001) rates compared with patients without RT. The subgroup analysis on 35 patients who received rituximab plus chemotherapy showed that RT did not improve the 5-year OS (88 vs. 92%; P=0.814) or the 5-year PFS (78 vs. 65%; P=0.511) rates compared with patients without RT. On multivariate analysis, RT and the addition of rituximab were predictive of increased OS [RT: Hazard ratio (HR), 0.157; P=0.018; rituximab: HR, 0.156; P=0.009] and PFS (RT: HR 0.111, P=0.001; Rituximab: HR 0.231, P=0.002) rates. However, the role of RT in PMLBCL in the rituximab era is unclear. Further investigation of the role of RT in the era of targeted therapy is required.